2012
DOI: 10.1038/ijo.2012.91
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide improves hippocampal synaptic plasticity associated with increased expression of Mash1 in ob/ob mice

Abstract: Liraglutide elicits beneficial effects on metabolic control and synaptic plasticity in mice with severe obesity and insulin resistance mediated in part through increased expression of Mash1 believed to improve hippocampal neurogenesis and cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 56 publications
(80 reference statements)
4
46
1
Order By: Relevance
“…Our behavioral data demonstrating impaired spontaneous alternation in a T-maze in HFD mice provides additional support for hippocampal-based memory dysfunction resulting from HFD, complementing other spatial and non-spatial memory tasks used in the aforementioned studies. Moreover, neurophysiological studies have found both LTP and LTD deficits in models of Type I and II diabetes, including streptozotocin, Zucker rat, db/db, ob/ob and HFD-induced models (Artola et al, 2005; Finger et al, 2010; Gispen and Biessels, 2000; Ho et al, 2012; Hwang et al, 2010; Li et al, 2002; Porter et al, 2012a; Porter et al, 2012b; Stranahan et al, 2008; Winocur and Greenwood, 2005) further corroborating our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our behavioral data demonstrating impaired spontaneous alternation in a T-maze in HFD mice provides additional support for hippocampal-based memory dysfunction resulting from HFD, complementing other spatial and non-spatial memory tasks used in the aforementioned studies. Moreover, neurophysiological studies have found both LTP and LTD deficits in models of Type I and II diabetes, including streptozotocin, Zucker rat, db/db, ob/ob and HFD-induced models (Artola et al, 2005; Finger et al, 2010; Gispen and Biessels, 2000; Ho et al, 2012; Hwang et al, 2010; Li et al, 2002; Porter et al, 2012a; Porter et al, 2012b; Stranahan et al, 2008; Winocur and Greenwood, 2005) further corroborating our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Spatial memory deficits have been reported in genetic models employing the leptin-receptor mutant db/db mouse and Zucker rat (Li et al, 2002; Winocur and Greenwood, 2005), while leptin-deficient ob/ob mice have been reported to show normal memory (Finger et al, 2010; Porter et al, 2012b). HFDs have been reported to cause impairments in cognitive behaviors in rats (Greenwood and Winocur, 1990; Stranahan et al, 2008) and in many, but not all mouse model studies (Boitard et al, 2012; Heyward et al, 2012; Hwang et al, 2010; Morrison et al, 2010; Pistell et al, 2010; Porter et al, 2012a; Porter et al, 2010; Tucker et al, 2012; Valladolid-Acebes et al, 2011; Yamada-Goto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, locomotor activity was decreased in the light phase by both (pGlu-Gln)-CCK-8 and [D-Leu-4]-OB3, but not by combined treatment, which is intriguing and merits further investigation. Energy expenditure was also decreased by (pGlu-Gln)-CCK-8, which could be a direct reflection of decreased activity [47]. Nonetheless, given the prominent effects of (pGlu-Gln)-CCK-8 on body weight reduction, elevations of energy expenditure might have been predicted, although measurements were made on day 18 when body weight regulation appears to have stabilised.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that treatment of exedin-4, a GLP-1 mimetic, improves the impaired learning and memory performance, and also ameliorates tau hyperphosphorylation induced by STZ ICV (Chen et al, 2012a). Liraglutide, another analog of GLP-1, has been shown to rescue hippocampal LTP that is severely impaired in ob/ob mice (Porter et al, 2013). The same drug that reverses the neurological impairments in mouse models of diabetes has also shown good effects in an APP/PS1 mouse model of AD.…”
Section: Therapeutic Methodologies Tested On Animal Modelsmentioning
confidence: 98%
“…Thus, the ob/ob mouse strain can serve as a model for AD-related changes in the brain linked to low levels of leptin. A study of ob/ob mice has suggested that long-term potentiation (LTP) induced in area CA1 is completely abolished in ob/ob mice compared with lean controls (Porter et al, 2013). Another study has shown that ob/ob mice performed an anxious behavior in an elevated plus maze, and that this effect could be reversed with the administration of leptin (Asakawa et al, 2003).…”
Section: Transgenic Diabetic Rodents Ob/ob Transgenic Micementioning
confidence: 98%